Insights from scientometrics and text analysis on the management of inclusive education in higher education - Matridi, Matridi (Journal of Interdisciplinary Studies in Education, 2026)
This study employs scientometric and text-analytic approaches to map the management of inclusive education, encompassing a review of scientific publications from 1997 to 2024. The data show significant publication growth, with an annual growth rate of 19.02%, and 736 documents published by 1,934 authors across 736 sources. The analysis results showed an average citation per document of 7,876, reflecting the field’s high impact. The annual scientific production chart shows a stable initial phase through 2010, followed by a significant increase after 2016, peaking in 2023. An analysis based on Bradford’s law revealed that most articles originated from a small number of core journals. In contrast, network analysis identified relationships between key topics such as “inclusive education,” “students,” and “technology.”